Chemical transformations in the transmission electron microscope - Fung, Kayleigh L Y (2021)
The transmission electron microscope (TEM) is routinely used to study the nanoscale structure of many types of materials. The high energy electron beam can impart some or all of its energy to the sample which can be useful for analysis (for example in electron energy loss spectroscopy) or not (when unwanted beam damage occurs). Throughout this thesis, the electron beam was used to initiate chemical transformations which was followed in situ using imaging, diffraction, and spectroscopy. Electron-transparent, nanometre-thick materials are the ideal samples for studying beam-induced chemical transformations because heating and charging effects are minimised. Individual molecules of perchlorocoronene (PCC), a polycyclic aromatic hydrocarbon (PAH), were imaged over time by encapsulating them inside single- walled carbon nanotubes (SWNTs). These image series were used to study the kinetics of the beam-induced polymerisation of PCC inside SWNTs. In-situ heating and cryogenic experiments allowed us to study the effects of temperature on these PCC polymerisations. Nanoscale crystals of hexaazatrinaphthylenes (HATs), another type of PAH, were irradiated under constant electron flux (electrons nm−2 s−1) in order to understand their stabilities and reactivities. HATs can be building blocks for organic frameworks and the electron beam can be used to crosslink aromatic molecules in electron beam lithography (EBL). Understanding HAT reactivity under the electron beam and combining this with EBL could lead to a straightforward method of synthesising HAT-derived organic frameworks in bulk. The product of irradiating the endohedral fullerene HF@C60 was investigated using imaging, diffraction, and spectroscopy in the TEM. It is likely that a trapped radical, F@C60, is generated under irradiation. Developing a new method of processing the TEM sample allowed us to analyse the specific irradiated area using another technique: optically detected magnetic resonance (ODMR). This technique can be used to detect radicals using fluorescence and is capable of nanoscale resolution through use of nitrogen vacancies in nanodiamonds (which exhibit ODMR behaviour). TEM and ODMR together may be useful for characterisation and analysis of many different materials.